(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2023)
Cybersecurity is a technical field and one that at its core, requires strong quantitative skills. This paper is all about how mathematics is used in cybersecurity. Most cybersecurity studies generally require basic mathematics concepts that are used in binary, cryptography, or some minimal programming tasks.This paper gives an introduction to a realistic problem of current cyberspace i.e. cyber-attacks and defense. Description of the objects used for cyber-attacks and tell the means of spreading them such as secondary memory, e-mail attachments, instant messages or malicious bots. Roll of mathematical modeling and simulation to solve the problem with an extensive literature review. A cyber defense architecture and possible elements of cyber defense model are also studied for finding the research gaps. After surveying a wide range of cyber security issues, I come to the conclusion that the field of cyber security gives rise to a rich set of new and exciting research opportunities for the mathematical and statistical techniques.